Preclinical Determinants of Drug Choice under Concurrent Schedules of Drug Self-Administration - Matthew L. Banks; S. Stevens Negus (Advances in Pharmacological Sciences)
Drug self-administration procedures have played a critical role in the experimental analysis of psychoactive compounds, such as cocaine, for over 50 years. While there are numerous permutations of this procedure, this paper will specifically focus on choice procedures using concurrent schedules of intravenous drug self-administration. The aims of this paper are to first highlight the evolution of drug choice procedures and then review the subsequent preclinical body of literature utilizing these choice procedures to understand the environmental, pharmacological, and biological determinants of the reinforcing stimulus effects of drugs. A main rationale for this paper is our proposition that choice schedules are underutilized in investigating the reinforcing effects of drugs in assays of drug self-administration. Moreover, we will conclude with potential future directions and unexplored scientific space for the use of drug choice procedures.